NEUROSCIENCE APPLIED TO LEARNING AS AN INTERVENTION IN SENSORY SYSTEM DYSFUNCTIONS BY OCCUPATIONAL THERAPISTS (REMUNOM, 2025)
Inclusion has been widely discussed in contemporary society and is addressed in official documents that provide for the integration of students with special educational needs into regular classrooms, with complementary support in specialized environments. Objective: To understand how neuroscience can be applied to the teaching and learning process of students with cognitive deficits through pedagogical practices that promote cognitive development under the guidance of an occupational therapist. Methodology: A qualitative, bibliographic approach based on the analysis of scientific articles, books, theses, and dissertations published in the last five years, accessed in public and free databases, using the keywords: neuroscience, cognitive deficit, occupational therapy, brain plasticity. Results: Activities that simultaneously stimulate different brain areas—such as music, movement, and art—significantly contribute to the development of cognitive skills in students with cognitive deficits. Neuroscience indicates that the use of educational games can enhance learning, especially when combined with practices that require motor coordination and concentration, promoting greater knowledge acquisition through neuroplasticity. The integration of occupational therapy, pedagogical practices, and neuroscience enables more effective and interactive approaches capable of activating different brain areas. Welcoming and adapted environments significantly contribute to improving these students’ occupational performance. Conclusion: The articulation between neuroscience, pedagogical practices, and occupational therapy is fundamental to enhancing the learning of students with cognitive deficits through playful strategies such as games, music, and art, as well as to stimulate and strengthen neuroplasticity